Technical evaluation of supercritical fluid impregnation scaling-up of olive leaf extract: From lab to pilot scale - Noelia D. Machado; Lidia Verano-Naranjo; Cristina Cejudo-Bastante; Casimiro Mantell-Serrano; Lourdes Casas-Cardoso (Journal of CO2 Utilization, 2024)
Supercritical fluid technology is an advanced field that offers remarkable versatility and it applies to a broad range of processes. However, the scaling-up of the supercritical fluid impregnation process is still scarcely explored. This research investigates the technical analysis of the supercritical fluid impregnation scaling-up of olive (Olea europaea L.) leaf extract into polypropylene (PP) films. The impregnation scale was increased up to 20-fold while maintaining constant ratios among the extract volume, film area, CO2 amount, and vessel geometry. The study compares homogeneity, total extract loading, and ABTS antioxidant activity of impregnated films at both scales. Homogeneity was assessed using CIELAB coordinates and desorption electrospray ionization mass spectroscopy (DESI-MS) imaging. Films impregnated at 250 bar and 55 °C for 1 h in 100 ml and 500 ml vessels were uniform in colour, whereas those from the larger vessel were less homogeneous. To evaluate the effect of time on impregnation at the largest scale, impregnation was conducted for 1, 6, 24, and 48 h. Homogeneity and ABTS antioxidant activity improved over time, and DESI-MS images showed a gradual decrease in oleuropein signal intensity over time. After 6 h, PP films achieved a total extract loading of 14.02 mg g−1 of polymer, 23 % ABTS antioxidant activity, with a global diffusion coefficient of the extract compounds in PP films of 3.42 × 10−13 m2 s−1. While this study offers valuable insights into scaling up the supercritical fluid impregnation of olive leaf extract into PP films, several limitations remain. Future research is required for a more comprehensive understanding and practical application of the process.